Sang Pandai Tutur Kata : Nabi Harun AS / Yugha Erlangga, Tim Emir ; editor, Fikni Mutiara, Hijrah Ahmad, Andhika Prasetya - Yugha Erlangga; Tim Emir; Fikni Mutiara; Hijrah Ahmad; Andhika Prasetya (Erlangga, 2015)
42 hlm. : ilus. ; 21 cm.